Assessing the Socioeconomic Impacts of Drought in the Southeast of Afghanistan - Mangal, Mohammad Rafiq; Mushwani, Hayatullah; Arabzai, Abidullah; Ullah, Hayat (Journal of Natural Sciences – Kabul University, 2026)
In Afghanistan, drought is one of the leading natural disasters with socioeconomic consequences. According to the Afghanistan disasters management profile, drought is one of the potential disasters in Afghanistan with multifaceted impacts. The present study was carried out in the Gaghori District, Ghazni province of Afghanistan to assess the socioeconomic impacts of drought. The study was conducted using quantitative research methodology where 386 respondents were surveyed using a cross-sectional survey. The survey questionnaire was based on three primary variables (public awareness, social impact, and economic impact). Content validity and reliability were examined for precision. The study utilized a random sampling technique with a 5% margin of error and a confidence interval of 95%. The results revealed that 88.71% of the respondents were aware of drought hazards. 47.63 % and 95.70 % experienced social and economic impacts of drought. The findings revealed correlation between community awareness and drought impacts of drought.